Composting: A Writing Practice of Wellness for Academics of Color. (3rd July 2022) - Moses, Michael W.
Abstract : Despite documented accounts from academics of color, literature about academic writing often overlooks their experiences as racially minoritized writers. This article addresses this limitation by situating Natalie Goldberg's (2016 ) composting as a writing practice of wellness. I begin by defining composting as an active process of leveraging patience and trusting time writers of color can use to liberate themselves from the academy's hyper-competitive and racialized standards. I then describe my personal journey with composting as an illustrative case to consider how the practice aligns with the needs of writers of color. Thereafter, I name three practical approaches to composting designed to push a writer's work forward and simultaneously care for their wellness. I conclude with a discussion of composting's significance for not only academics of color but also understandings of academic writing more broadly.